Barriers Against Mammographic Screening in a Socioeconomically Underdeveloped Population: A Population-based, Cross-sectional Study - ÖZAYDIN, AYŞE NİLÜFER (AVES, 2016)
Objective: Mammography-screening (MS) rates remain low in underdeveloped populations. We aimed to find the barriers against MS in a low socioeconomic population. Materials and Methods: Women aged 40-69 years who lived in the least developed city in Turkey (Mus), were targeted. A survey was used to question breast cancer (BC) knowledge and health practices. Results: In total, 2054 women were surveyed (participation rate: 85%). The MS rate was 35%. Women aged 50-59 years (42%, p<0.001), having annual Obstetric-Gynecology (OB-GYN) visits (42%, p<0.001), reading daily newspaper (44%, p=0.003), having Social Security (39%, p=0.006) had increased MS rates. The most common source of information about BC was TV/radio (36%). Having doctors as main source of information (42%, p<0.001), knowing BC as the most common cancer in females (36%, p=0.024), knowing that BC is curable if detected early (36%, p=0.016), knowing that MS is free (42%, p<0.001) and agreeing to the phrase I would get mammography (MG), if my doctor referred me (36%, p=0.015) increased MS rates. Agreeing that MG exposes women to unnecessary radiation decreased MS rate (32%, p=0.002). Conclusion: To increase the MS rate in low socioeconomic populations, clear messages about BC being the most common cancer in women, MS after 40 years of age not causing unnecessary radiation but saving lives through enabling early detection, and MS being free of charge should be given frequently on audiovisual media. Uninsured women and women aged 40-49 years should be especially targeted. Physicians from all specialties should inform their patients about BC.
Keywords: Breast cancer; screening; prevention; cross-sectional studies; BREAST SELF-EXAMINATION; CANCER PATIENTS; WOMEN; ADHERENCE; RELATIVES; BELIEFS; BEHAVIORS; AGE